Plant biomacromolecule delivery methods in the 21st century - Rustgi, Sachin; Naveed, Salman; Windham, Jonathan; Zhang, Huan; Demirer, Gözde S. (Frontiers in Genome Editing, 2022)
The 21st century witnessed a boom in plant genomics and gene characterization studies through RNA interference and site-directed mutagenesis. Specifically, the last 15 years marked a rapid increase in discovering and implementing different genome editing techniques. Methods to deliver gene editing reagents have also attempted to keep pace with the discovery and implementation of gene editing tools in plants. As a result, various transient/stable, quick/lengthy, expensive (requiring specialized equipment)/inexpensive, and versatile/specific (species, developmental stage, or tissue) methods were developed. A brief account of these methods with emphasis on recent developments is provided in this review article. Additionally, the strengths and limitations of each method are listed to allow the reader to select the most appropriate method for their specific studies. Finally, a perspective for future developments and needs in this research area is presented.